Detection of Morphometric Differentiation of Liza aurata (Pisces: Mugilidae) in Southeastern of the Caspian Sea, Iran - Kohestan-Eskandari, S.; AnvariFar, H.; Mousavi-Sabet, H. (Our Nature, 2014)
A 13-landmark morphometric truss network system was used for 135 specimens to investigate the hypothesis differentiation of golden grey mullet along the southeastern Caspian Sea. Univariate analysis of variance showed significant differences among the means of the three groups for 35 standardized morphometric measurements out of 78 characters studied. In linear discriminant function analysis (DFA), the overall assignment of individuals into their original groups was 66.7%. The proportions of individuals correctly classified into their original groups were 62.5%, 59.1%, 76.5% in Neka, Behshahr and Galogah populations, respectively. The Principal Component Analysis (PCA) showed that the specimens grouped into 2 areas with high degree of overlap. Clustering analysis based on Euclidean square distances among the studied groups of centroids using an UPGMA resulted segregation of the three populations into two distinct clusters. These results could be of interest for management and conservation programs of this species in the Caspian Sea. DOI: http://dx.doi.org/10.3126/on.v11i2.9595 Our Nature 2013, 11(2): 126-157